YIELD AND QUALITY OF SILAGE FROM SOYBEAN-MAIZE INTERCROPPING - Yücel, Celal; Avcı, Mustafa; Kızılşimşek, Mustafa; Hatipoğlu, Rüştü (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Production of good quality fodder is of a great importance for the economical ruminant production. The present experiment was carried out to study the effects of different sowing patterns and harvest times on digestibile dry matter yield, crude protein yield and feed quality of silages from intercropped soybean (Glycine max L.) and maize (Zea mays L.) systems. A split-plot experiment (8 sowing patterns x 2 harvest times) in randomized block design was established at the Experimental Area of Eastern Mediterranean Agricultural Research Institute in Adana, Turkey, during the growing seasons of 2010 and 2011. The sowing patterns were (1) 1 row maize to 1 row soybean (1M-1S), 2) 1 row maize to 2 rows soybean (1M-2S) 3) 2 rows maize to 1 row soybean (2M-1S) 4) 50 % maize+% 50 soybean in the same row 5) 33.3 % M+66.6 % S in the same row 6) 66.6 M+33.3S in the same row 7) sole soybeans 8) sole maize. The forage was harvested at the milk and dough stages of the maize dents. Results of the study showed that the mixture of 66.6 % maize + 33.3 soybean in the same row when harvested at dough stage could be suggested for higher digestible dry-matter yield with improved silage quality.
Keywords: Harvest time; Corn-soybean intercropping; Sowing pattern; Yield; Silage quality